Métodos alternativos de resolução de conflitos empresariais - Melo, Fernanda Cardoso de (2021)
This dissertation concerns the Concentration Area “Justice, Company and Sustainability”, in Research Line 2: “Company, Sustainability and Functionalization of Law”. The present dissertation is of the descriptive type and developed based on the inductive method. The work is based on bibliographic research, articles published in electronic journals and research on online platforms. With regard to the structure of the work, it will be divided into five chapters and subdivided into topics to improve the understanding of each subject addressed. This work aims to analyze alternative methods, such as conciliation, mediation and arbitration as solutions to help resolve conflicts and ease the slowness in the Brazilian Judiciary System, because, alone, it is unable to resolve all the demands that are presented in court. The accumulation of lawsuits and exaggerated formalism slow down the Judiciary and, therefore, other means are necessary for the composition of conflicts. The emergence of other movements is of paramount importance to guarantee access to justice. Thus, it is necessary to reflect on other ways to seek legalization and enable results that contribute to efficient and quality justice. Thus, it is concluded that consensual methods for resolving disputes are important to avoid congestion in the Judiciary. Thus, it will be necessary to consider that disputes can be resolved by other tools than state jurisdictional protection, but, for that, it will be necessary to modify the culture of society according to which the decision can only be made by the State-Judge.